Cellugyrin (synaptogyrin-2) dependent pathways are used by bacterial cytolethal distending toxin and SARS-CoV-2 virus to gain cell entry - Boesze-Battaglia, Kathleen; Cohen, Gary H.; Bates, Paul F.; Walker, Lisa M.; Zekavat, Ali; Shenker, Bruce J. (Frontiers in Cellular and Infection Microbiology, 2024)
Aggregatibacter actinomycetemcomitans cytolethal distending toxin (Cdt) is capable of intoxicating lymphocytes, macrophages, mast cells and epithelial cells. Following Cdt binding to cholesterol within lipid rafts, subunits are internalized and traffic to intracellular compartments; the latter events are dependent upon, cellugyrin, a critical component of synaptic like microvesicles (SLMVCg+). Target cells, such as Jurkat cells, rendered unable to express cellugyrin are resistant to Cdt-induced toxicity. Similar to Cdt, SARS-CoV-2 entry into host cells is initiated by binding to cell surface receptors associated with cholesterol-rich lipid rafts; this association leads to fusion and/or endocytosis of viral and host cell membranes and intracellular trafficking. The similarity in internalization pathways for both Cdt and SARS-CoV-2 led us to consider the possibility that cellugyrin was a critical component in both processes. Cellugyrin deficient Calu-3 cells (Calu-3Cg-) were resistant to infection by VSV/SARS-CoV-2-spike pseudotype virus and partially resistant to VSV/VSV-G pseudotype virus. Synthetic peptides representing various regions of the cellugyrin protein were prepared and assessed for their ability to bind to Cdt subunits and SARS-CoV-2 spike protein using surface plasmon resonance. Binding specificity was further analyzed using cellugyrin scrambled peptide mutants. We propose that SLMVCg+ represent a component of a common pathway that facilitates pathogen and/or pathogen-derived toxins to gain host cell entry.